EFEK ASAM METOKSIASETAT TERHADAP PERKEMBANGAN EMBRIO PRAIMPLANTASI DAN KUALITAS BLASTOKISTA MENCIT (MUS MUSCULUS) SWISS WEBSTER - PRIYANDOKO, DIDIK
The effects of MAA on the development of pre-implantation embryos, number of blastocyst cells, mitotic index and ploidy of chromosome of blastocyst cells in Swiss Webster mice (Mus muscuhus) have been studied. Female mice were superovulated with 5 IU of PMSG (Folligon) and 5 IU of hCG (Chorulon) and were mated with male mice overnight. A vaginal plug detected the following morning was confirmed as day 0 of gestation. On gestation day 2, mice were adsministered with MAA dose 1.75, 2.0 or 2.3 mmol/kg body weight (bw) by gavage. On gestation day 3.5, mice were sacrificed for embryo collection. Observation on the number of 1-8 cell, uncompacted morula, compacted morula, early blastocyst, late blastocyst and abnormal embryos were done on gestation day 3.5. Total number of cells which composed late blastocysts, and mitotic index, were done on disaggregated late blastocysts using Tarkowski's method. The results showed that MAA 2.0 or 2.3 mmol/kg bw significantly decreased (p<0.05) the percentage of embryos that reached late blastocyst. MAA dose 2.0 or 2.3 mmol/kg bw also significantly increased (p<0.05) the percentage of early blastocyst. The total percentage of the abnormal embryos from dams treated with MAA dose 1.75, 2.0 or 2.3 mmol/kg bw significantly increased (p<0. 05). The results also showed that all doses of MAA significantly (p< 0.05) the total number of late blastocyst cells as well as the mitotic index. Flow cytometry analysis on about 10000 blastomer from dams treated with MAA 2.3 mmol/kg bw showed that 58.01 % of the blastocyst cells were diploid and 41.99% were aneuploid, whereas in the control 100 % were diploid. It could be concluded that the administration of MAA on gestation day 2 inhibits the development of the pre-implantation mouse embryos proven by the decrease of the percentage of embryos reaching late blastocyst stage caused by developmental retardation, especially at early blastocyst stage and the increase of abnormal embryos. MAA could significantly decrease the cell number of blastocyst, the mitotic index and causes aneuploidy.